Biodeterioration process of chromium tanned leather with Penicillium sp. (January 2017) - Zhang, Jinwei; Han, Zhangwei; Teng, Bo; Chen, Wuyong
Abstract: For getting a clear and detail process of chromium tanned leather biodeteriorated with Penicillium sp. as a reference for future research and providing a cleaner chromium containing leather waste disposal method. The chromium tanned leather (CTL) and chromium tanned hide powder (CTHP) were biodeteriorated with the Penicillium . The CTL was biodeteriorated at first to verify the biodeterioration effect, and then the changes of the CTHP structure and thermal properties after the biodeterioration were analyzed by Scanning Electron Microscope (SEM), Fourier transform infrared spectroscopy (FT-IR), Thermal Gravimetric Analyzer (TG) and Differential Scanning Calorimeter (DSC). The deterioration degree of the CTHP was characterized by the contents of hydroxyproline and total nitrogen in the filtrate, the Penicillium number was counted too during the process. The results showed that the CTL could be biodeteriorated with the Penicillium as shrinkage temperature and mass decreasing even though the biodeterioration degree was not ideal enough. After the process of CTHP biodeteriorated with the Penicillium, the surface morphology and structure of the CTHP were damaged. The thermal resistance and thermal denaturing temperature reduced which showed the detanning effect happened in the biodeterioration process. With the increasing of biodeterioration time, the hydroxyproline and total nitrogen in the filtrate increased. The Penicillium number maximized at 96 h and protease was produced in the process with enzymatic activity reaching to 9.23U mL −1 . These phenomena demonstrated the Penicillium grew through digesting chromium tanned leather and produced metabolites. To sum up, the biodeterioration process of chromium tanned leather with Penicillium was a synergistic effect of chromium detanning and the Penicillium growth. Highlights: The biodeterioration process is a synergistic effect of detanning and microbe growth. The detanning and Penicillium sp. growth promote each other in biodeterioration process. The study could be reference and possible choice for future research and utilization.